STRATEGY TO STRENGTHEN HIGHER EDUCATION COMPETITIVENESS: AT UNIVERSITAS ISLAM SYKH-YUSUF TANGERANG INDONESIA - M. Yus Firdaus (International Journal of Social Science, 2024)
Institutions of higher education to be able to compete among other institutions, both state and private, must transform by finding formulations and innovations according to the character of each superior institution. Higher education can improve their reputation and positive brand image by developing a marketing strategy for educational services. The purpose of this study is to reveal strategies for improving brand image and competitiveness in marketing at Higher Education. This study uses a qualitative approach. Data collection was carried out using interview, observation and documentation techniques. The results of the study indicate that: (1) service quality; (2) customer satisfaction; (3) understanding or cognition; (4) competitive prices; (5) product quality; (6) product excellence; (7) service quality; (8) customer satisfaction; and (9) self-awareness (behavioral intentions) are indicators of strategies for strengthening the competitiveness of higher education which have provided benefits for higher education organizations